Tryptophan rich diet as a new approach to study the serotoninergic enteropancreatic axis. (1987) - Goke, B; Richter, G; Keim, V; Arnold, R
Abstract : The influence of a tryptophan enriched diet (L-tryptophan added as 1% of total diet), fed over 10 days, on the rat duodenum and pancreas was studied by immunohistology, measurements of serotonin and tryptophan tissue concentrations by HPLC, and incubations of pancreatic lobules. Ingestion of a tryptophan enriched diet resulted in increased contents of tryptophan and serotonin in the duodenum that was not accompanied by a significant change of the serotonin cell density. Neither basal nor CCK-stimulated amylase release from isolated pancreatic lobules was altered after tryptophan enriched food. Although serotonin could be extracted from the pancreas, no increase in serotonin concentration was detected after ingestion of the tryptophan diet. A 'serotonin loading' diet may be a useful tool to study the significance of amines produced by gut endocrine cells in respects to enteropancreatic connections.